Accidental discovery of copy number variation on chromosome 1 in a fetus with high risk of trisomy 13 suggested by NIPT - Chang, Jiazhen; Song, Yingna; Qi, Qingwei; Hao, Na; Liu, Juntao (Zhonghua yi xue yi chuan xue za zhi, 2023)
To validate a fetus with high risk for trisomy 13 suggested by non-invasive prenatal testing (NIPT). The fetus was selected as the study subject after the NIPT detection at Peking Union Medical College Hospital, Peking Union Medical College and Chinese Academy of Medical Sciences on February 18, 2019. Clinical data of the pregnant woman was collected. Fluorescence in situ hybridization (FISH), chromosomal karyotyping analysis and chromosomal microarray analysis (CMA) were carried out on amniotic fluid and umbilical cord blood and the couple's peripheral blood samples. Copy number variation sequencing (CNV-seq) was also performed on the placental and amniotic fluid samples following induced labor. The pregnant woman, a 38-year-old G4P1 gravida, was found to have abnormal fetal development by prenatal ultrasonography. NIPT test suggested that the fetus has a high risk for trisomy 13. Chromosomal karyotyping analysis of fetal amniotic fluid and umbilical cord blood were 46,XN,add(13)(p10). The result of CMA was